Plasma surface treated polyvinylidenefluoride - trifluoro ethylene (PVDF-TrFE) copolymer films / Muhamad Naiman Sarip - Sarip, Muhamad Naiman (2016)
PVDF-TrFE films with thickness of 200 nm were produced by spin coating with solution concentration of 30 g/L and spinning rate of 1500 rpm. Surface of treated PVDF-TrFE film with pressure of 0.6 mbar at 9 minutes exposure time showed large elongated crystallite with increased average surface roughness from 3.51 nm to 9.12 nm. Meanwhile surface of PVDF-TrFE film treated with pressure of 0.3 mbar at 9 minutes exposure time showed a very fine crystal growth with average surface roughness of 5.60nm. Contact angle dropped significantly after plasma treatment. Exposure time of 9 minutes showed high reduction of contact angle (33%). Contact angle measurement returned to its original state after 5 days of treatment indicating that the surface with high surface energy was less stable. The FTIR spectrum indicated peaks at 1292, 848 and 885 cm"1 , which showed significant increased in intensity. These peaks represented all trans (TTTT) configurations. These showed that surface treatment had increased the presence of Pphase crystals on the surface of the treated PVDF-TrFE films. These P-phase crystals contributed to increment in the dielectric constant measurements. Dielectric constant at frequency of 10ᶟ Hz showed high increment from 10.5 to 17.0 with very low tan 5 of 0.15. Elemental composition on surface treated PVDF- TrFE film detected group of fluorine at 695.3eV, oxygen group at 540.8eV and carbon group at range from 313ev to 263ev. Reduction of F/C ratio indicated dehydrofluorination on the surface, whilst the increased in O/C ratio suggested that plasma treated PVDF-TrFE film surface had interacted with oxygen in the environment. Thus, it is concluded that plasma treated PVDF-TrFE film with pressure of 0.6mbar and exposure time of 9 minute was the optimized film required for producing film surface with high surface energy, high surface roughness and high dielectric properties. However, immediate application after plasma treatment is highly recommended in order to prevent any surface oxidation.